Candide a comic operetta in two acts - Bernstein, Leonard 1918-1990 (Kultur, 2009)
Leonard Bernstein's comic operetta is based on the classic Voltaire tale of an innocent young man's journey through a life filled with colorful characters and unexpected life lessons.